Evidence of acceptability of oral paediatric medicines: a review. (14th August 2016) - Mistry, Punam; Batchelor, Hannah
Abstract: Objectives: The aim of this review was to map the currently available evidence on acceptability of oral paediatric medicines to aid in the selection of suitable platform formulations for the development of new acceptable paediatric products. Methods: This process used a defined search strategy of indexed publications and included methods to assess the quality of the evidence retrieved. Key findings: Taste/palatability was the most extensively studied area of paediatric medicine acceptability yet standard methods or criteria that define what is classed as acceptable to children is still to be defined. There have been many reports on the acceptability of medicines to paediatric populations yet major gaps in the acceptability knowledge base exist including the shape and dimensions of tablets, minitablets and capsules swallowed whole in infants and children; size and overall volume of multiparticulates; volume of liquids completely swallowed in infants and children; duration of retention within the oral cavity, size and taste of orodispersible tablets, lozenges and chewable tablets and the number of solid units dosed at each time point. Conclusions: The review highlights where further information is required to support knowledge around acceptability of age-appropriate medicines. An algorithm to aid in selection of a formulation that is likely to be acceptable based on the age range to be treated by the medicine is presented as a result of this review.